Analisis Perbandingan Kinerja Protokol Routing RIP dan Protokol Routing IS-IS pada IPv4 dan IPv6 - Rino Erik Sanrio; Primantara Hari Trisnawan; Fariz Andri Bachtiar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
RIP and IS-IS are routing protocols with round trip times and the fastest convergence time among other dynamic routing protocols. Workflow and routing protocol performance is affected by the algorithm used. GNS3 is a simulator used for simulating routing protocols with mesh topologies. This study uses Wireshark to record packets on the network. This routing protocol is implemented using IPv4 and IPv6 addressing. Tests carried out using mesh topology 4 routers and 6 routers. Convergence time and round-trip time are the performance parameters that are tested. This study aims to determine the convergence process when the path is broken. The results of the research are the IS-IS routing protocol that uses IPv4 addressing has the fastest convergence time with a convergence time of 0 ms, while the RIP routing protocol is 1 ms. This is because the algorithm used makes the IS-IS router has a database that connects the network topology.